Impacts of Elevated Atmospheric CO2 and O3 on Paper Birch (Betula papyrifera): Reproductive Fitness - Joseph N. T. Darbah; Mark E. Kubiske; Neil Nelson; Elina Oksanen; Elina Vaapavuori; David F. Karnosky (The Scientific World Journal)
Atmospheric CO2 and tropospheric O3 are rising in many regions of the world. Little is known about how these two commonly co-occurring gases will affect reproductive fitness of important forest tree species. Here, we report on the long-term effects of CO3 and O3 for paper birch seedlings exposed for nearly their entire life history at the Aspen FACE (Free Air Carbon Dioxide Enrichment) site in Rhinelander, WI. Elevated CO2 increased both male and female flower production, while elevated O3 increased female flower production compared to trees in control rings. Interestingly, very little flowering has yet occurred in combined treatment. Elevated CO2 had significant positive effect on birch catkin size, weight, and germination success rate (elevated CO2 increased germination rate of birch by 110% compared to ambient CO2 concentrations, decreased seedling mortality by 73%, increased seed weight by 17%, increased root length by 59%, and root-to-shoot ratio was significantly decreased, all at 3 weeks after germination), while the opposite was true of elevated O3 (elevated O3 decreased the germination rate of birch by 62%, decreased seed weight by 25%, and increased root length by 15%). Under elevated CO2, plant dry mass increased by 9 and 78% at the end of 3 and 14 weeks, respectively. Also, the root and shoot lengths, as well as the biomass of the seedlings, were increased for seeds produced under elevated CO2, while the reverse was true for seedlings from seeds produced under the elevated O3. Similar trends in treatment differences were observed in seed characteristics, germination, and seedling development for seeds collected in both 2004 and 2005. Our results suggest that elevated CO2 and O3 can dramatically affect flowering, seed production, and seed quality of paper birch, affecting reproductive fitness of this species.